Cognitive and behavioral correlates of depressive symptoms in a community sample of adolescents. (January 2020) - Pullmer, Rachelle; Zaitsoff, Shannon L; Coelho, Jennifer S
Research in adults demonstrates a positive association among obsessive–compulsive symptoms, eating pathology, cognitive distortions, and comorbid depressive symptoms. Given that adolescence is characterized by unique and rapid changes in biopsychosocial processes, it is imperative to elucidate the relationship between these variables in youth. In this cross-sectional study, we explored whether obsessive–compulsive symptoms, thought–action fusion, thought–shape fusion, and eating pathology would be positively associated with and predict depressive symptoms in a school-based community sample of adolescents ( n = 86; M age = 15.60). All study variables were positively correlated with depressive symptoms. Results indicated that obsessive–compulsive symptoms, thought–shape fusion, and eating pathology explained a significant proportion of variance in depressive symptoms, whereas thought–action fusion did not. In accordance with the cognitive behavioral model of psychopathology, these findings highlight the relationships between key interrelated correlates of depressive symptoms that may be pertinent targets for prevention and treatment efforts in adolescents.